The Implementation of Norsok Z-008 for Equipment Criticality Analysis of Gas Central Processing Plant - Dwi Priyanta; Nurhadi Siswantoro; Muhammad Badrus Zaman; Dimas Fajar Prasetyo (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2019)
The gas central processing plant as a facility used to process natural gas had a variety of components that were so complex and many in number. To reduce the risk of failure of these components it was necessary to carry out maintenance. But it would be very inefficient if all the components were treated at the same level, considering that there were so many and the human resources that were owned were very limited. Therefore, in taking care of these components it was necessary to prioritize them according to their critical level. In this research, in determining the critical level of a component using risk-based methods according to the available standards, namely NORSOK Z-008. By making a hierarchy and asset level register of all components, then the value of the probability rating and consequence rating was determined. So that the criticality ranking of each component was obtained according to the criticality risk matrix that was converted from the company's risk matrix, so that the critical level of the component was obtained in the levels of H (high), M (medium), and L (low). With the critical level of this component, the company did not need to take care of all the components. In this research, there was 33 equipment with 140 subunits/subsystems, and the total number of components was 674. Of the 674 components as many as 28 components had a critical level of H (high), 192 components had a critical level M (medium), and 454 components had L critical level (low) of each critical level that has been obtained, it is not necessary to carry out maintenance with the same level to all components. In this research, every component that has H (high) criticality level will be treated as a Preventive Maintenance, while a component with a critical level of M (medium) will be Preventive Maintenance if needed, and a component with L critical level (low) will be treated Corrective Maintenance.